EVALUATING THE CLINICAL AND HEMODYNAMICAL ACTION OF NEBIVOLOL IN CHRONIC HEART FAILURE - M. A. Gurevich; N. P. Sanina; T. F. Hohlova; V. I. Buvalcev (Российский кардиологический журнал, 2001)
A task of this research was to study the influence of nebivolol on hemodynamic parameters, clinical sympthoms and life quality in patients II-IV FK HD by NYHA. 24 patients of main group have taken nebivolol in daily dose of 2,5-5 mg per os. Patients were treated with the drug in a course of 3 months.A control group(15 people) was treated traditional therapy (by heart glicozides, metabolic preparations, diurethics, if necessary). We have found that new β-adrenoblocker with additional vasodilatatorial qualities- nebivolol (NEBILET) kindly influences main hemodinamic parameters in chronic coronary patients. During 3 months’ observation examined patients had KDR and KSR distinctly lowered, speed of shortening of miocardium fibrem and the function of throw and MV grew, tension in a pulmonary artery decreased. NEBILET’S prescription in dosage of 2,5-5 mg/ daily kindly influences the reduction of heart rythm’s disturbances, a distinct tendency to lowering of MMLV noted. NEBILET can be successfully used in a combinated therapy of CCD II-IV FK, its usage in cases of coronary deficiency and AG is mostly advisable.